2018
DOI: 10.1021/acsmedchemlett.8b00371
|View full text |Cite
|
Sign up to set email alerts
|

Potent Antimalarial 2-Pyrazolyl Quinolone bc1 (Qi) Inhibitors with Improved Drug-like Properties

Abstract: A series of 2-pyrazolyl quinolones has been designed and synthesized in 5−7 steps to optimize for both in vitro antimalarial potency and various in vitro drug metabolism and pharmacokinetics (DMPK) features. The most potent compounds display no cross-resistance with multidrug resistant parasite strains (W2) compared to drug sensitive strains (3D7), with IC 50 (concentration of drug required to achieve half maximal growth suppression) values in the range of 15−33 nM. Furthermore, members of the series retain mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…In 2018, Hong et al [ 103 ] reported a series of 2-pyrazolyl quinolone with activities on the bc1 (Qi) complex. They were based on their previous findings [ 104 ], where they had already identified compound 106 as one of the lead compounds of a new family ( Figure 14 ).…”
Section: Malaria Focused Mitochondrial Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, Hong et al [ 103 ] reported a series of 2-pyrazolyl quinolone with activities on the bc1 (Qi) complex. They were based on their previous findings [ 104 ], where they had already identified compound 106 as one of the lead compounds of a new family ( Figure 14 ).…”
Section: Malaria Focused Mitochondrial Targetsmentioning
confidence: 99%
“…The authors consider compound 102a as a new hit for the development of lead compounds targeting the P. falciparum mitochondrial bc1 complex. In 2018, Hong et al [103] reported a series of 2-pyrazolyl quinolone with activities on the bc1 (Qi) complex. They were based on their previous findings [104], where they had already identified compound 106 as one of the lead compounds of a new family (Figure 14).…”
Section: Developing Bc1 Antimalarial Inhibitorsmentioning
confidence: 99%
“…1 ) have been found 14 , 15 . A compound similar to RYL-552 bound at the Q i site of Pf bc 1 too, but it only very weakly inhibited Pf NDH2 16 . In addition to the generation of electrochemical gradient through the respiratory chain, a functional DHODH is also very important for malaria parasites' survival, as DHODH is essential for de novo biosynthesis of pyrimidine 8 .…”
Section: Introductionmentioning
confidence: 97%
“…Design and targets elucidation of multi-targeting inhibitors derived from RYL-552 will provide more powerful antimalarials than mono-targeting inhibitors for both curing symptoms and blocking transmission. On the other hand, as even subtle chemical transformations of the respiratory chain inhibitors can modify the targets selectivity 16 , 24 , 25 , some unclear results in previous studies need to be further clarified by mapping the inhibitor targets to efficiently guide antimalarial drug development 11 .
Figure 1 Mitochondrial respiratory chain of P. falciparum and its inhibitors.
…”
Section: Introductionmentioning
confidence: 99%
“…Further structure optimization efforts by Paul M. O'Neill's group have identified other analogs from this series with pyridyl or pyrazolyl group at C2 with enhanced potency. [13,14,15] Floxacrine (IV) and other acridone derivatives; hybrid of ciprofloxacin with antimalarial entities such as acridine and quinoline; 4(1H)-Quinolone ester ICI 56,780 (V); 4(1H)quinolone-3-diarylethers (VI) or their analogs are the other antimalarial quinolone chemotypes which have come up during lead optimization efforts (Figure 1). [4,10,[16][17][18][19][20][21][22][23][24] Though promising, many of these derivatives suffer from poor aqueous solubility and bioavailability.…”
Section: Introductionmentioning
confidence: 99%